2018
DOI: 10.7554/elife.35449
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell heterogeneity drives the parasitic life cycle of Schistosoma mansoni

Abstract: Schistosomes are parasitic flatworms infecting hundreds of millions of people. These parasites alternate between asexual reproduction in molluscan hosts and sexual reproduction in mammalian hosts; short-lived, water-borne stages infect each host. Thriving in such disparate environments requires remarkable developmental plasticity, manifested by five body plans deployed throughout the parasite’s life cycle. Stem cells in Schistosoma mansoni provide a potential source for such plasticity; however, the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
218
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(223 citation statements)
references
References 47 publications
4
218
1
Order By: Relevance
“…Recently, it was shown that schistosomula carry two types of stem cell populations: somatic stem cells and germinal cells 15 . The somatic stem cells are involved in somatic tissue differentiation and homeostasis during the parasite intra-mammalian development, whereas the germinal cells are presumed to give rise to germ cells (sperm and oocytes) in adult parasites 15 . Less than 24 hours after the cercaria enters the mammalian host to become schistosomulum, ~5 somatic stem cells at distinct locations begin to proliferate 15 (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, it was shown that schistosomula carry two types of stem cell populations: somatic stem cells and germinal cells 15 . The somatic stem cells are involved in somatic tissue differentiation and homeostasis during the parasite intra-mammalian development, whereas the germinal cells are presumed to give rise to germ cells (sperm and oocytes) in adult parasites 15 . Less than 24 hours after the cercaria enters the mammalian host to become schistosomulum, ~5 somatic stem cells at distinct locations begin to proliferate 15 (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…The somatic stem cells are involved in somatic tissue differentiation and homeostasis during the parasite intra-mammalian development, whereas the germinal cells are presumed to give rise to germ cells (sperm and oocytes) in adult parasites 15 . Less than 24 hours after the cercaria enters the mammalian host to become schistosomulum, ~5 somatic stem cells at distinct locations begin to proliferate 15 (Figure 5B). Germinal cells, on the other hand, are thought to be packaged in a distinct anatomical location called the germinal cell cluster, and only begin to proliferate ~ 1 week after penetrating the host 15 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations